Dangerous writing : the autobiographies of Willa Muir, Margaret Laurence and Janet Frame - Fuentes-Vásquez, Carmen Luz (Costerus, 2013)
This book examines the literary construction of personal identity through autobiographical narratives by three significant writers analysed together for the first time: the Scottish Willa Muir (1890-1970), the Canadian Margaret Laurence (1926-1987), and the New Zealander Janet Frame (1924-2004). These apparently dissimilar authors suffered not only geographical, but also political marginality: they were women from the working-class or struggling middle-class, striving to be considered as professional writers, and emerging from countries that might be felt to be under the shadows of economic an.